An Assistance to Project Risk Management Based on Complex Systems Theory and Agile Project Management. (10th October 2020) - Marle, Franck
Abstract : Project Risk Management is crucial in determining the future performance of a complex project. Increasing project complexity makes it more and more difficult to anticipate potential events that could affect the project and to make effective decisions to reduce project risk exposure. To tackle these conceptual and managerial issues, the proposed approach introduces Complex Systems Theory-based improvements into some PRM subprocesses and runs the global PRM process using Agile Project Management principles. We argue that these advanced techniques for managing project risk complexity, notably risk interdependencies, are coherent with the distributed, self-organized nature of agile teams. This new way of structuring and executing Project Risk Management offers the possibility to make decisions more frequently, when needed, with a more distributed authority, and with richer information about anticipation of events and consequences of actions. First results show an appropriation of this combined approach by project members due to agile principles that allows for getting the more reliable information promised by Complex Systems Theory.